Perbedaan Tingkat Kecemasan Antara Ibu yang Anaknya Kuliah di Luar Pulau dengan di Dalam Pulau di Kecamatan Kumai Kabupaten Kotawaringin Barat Provinsi Kalimantan Tengah - Mulyadi, Devi Van; , Prof. Dr. Moh. Fanani,dr. Sp.Kj (K); , dr. Anika Candrasari, M.Kes (2016)
Background: Mothers whose children study in the outer islands tend to be concerned about welfare of her child, increased economic needs due to the remote location and a long separation causing anxiety simptoms. Objectives: Analyzing the differences anxiety level between mothers whose children study in the outer islands with mothers whose children study in the island in the District Kumai West Kotawaringin Central Kalimantan Province. Methods: Reseach design is analytical observational with cross-sectional approach and use consecutive sampling. There are 96 respondents consist 48 mothers whose children study in the outer islands and 48 mothers whose children study in the island. The research used L-MMPI questionnaire to determine the number of lies and TMAS questionnaire to measure the level of anxiety. The avaible data were analyzed using t-test statistical test. Result: After analysis using t-test obtained value of p=0,000. There were statistically significant differences of anxiety level between mothers whose children study in the outer islands with mothers whose children study in the island in the District Kumai West Kotawaringin Central Kalimantan Province. Conclusion: Mothers whose children study in the outer islands have higher anxiety level than mothers whose children study in the island.